2013
DOI: 10.1111/bju.12229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and sonographic features predict testicular torsion in children: a prospective study

Abstract: Objective• To test the clinical and sonographic predictors of testicular torsion (TT) with the aim of reducing negative exploration rates. Patients and Methods• We performed a prospective study of all boys treated for 'acute scrotum' at our institute between January 2001 and April 2012 and clinical findings were documented.• If available, ultrasonography (US) was added to the diagnostic evaluation.• A prediction of the diagnosis was based on clinical and sonographic features, and was followed by surgical explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 19 publications
(41 reference statements)
4
70
0
1
Order By: Relevance
“…The left testis is involved in 60-66% of cases. 244,245 On gross examination the testis is usually diffusely hemorrhagic and edematous. In a case where an intra-abdominal testis in a 3-month-old infant underwent torsion, the cut surface showed multiple cystic cavities, one to several centimeters in diameter, corresponding to areas of hemorrhagic necrosis of the parenchyma.…”
Section: Testicular Torsionmentioning
confidence: 99%
“…The left testis is involved in 60-66% of cases. 244,245 On gross examination the testis is usually diffusely hemorrhagic and edematous. In a case where an intra-abdominal testis in a 3-month-old infant underwent torsion, the cut surface showed multiple cystic cavities, one to several centimeters in diameter, corresponding to areas of hemorrhagic necrosis of the parenchyma.…”
Section: Testicular Torsionmentioning
confidence: 99%
“…Several studies have demonstrated that the most reliable physical signs of TT include (a) a high-riding testis, (b) absent cremasteric reflex, and (c) an anteriorly rotated epididymis or abnormally oriented testis. 18,19,24 High-resolution ultrasound (HRUS) with color-flow Doppler ultrasonography (CDS) and radionuclide imaging can provide information about blood flow to the testes. 25 Absent arterial flow within the suspect testis on CDS is indicative of testicular torsion.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the most reliable physical signs of TT include (a) a high-riding testis, (b) absent cremasteric reflex and (c) an anteriorly rotated epididymis or abnormally oriented testis [18,19,24].…”
Section: Physical Findingsmentioning
confidence: 99%